Preheating in Palatini Higgs inflation on the lattice. Issue 9 (1st September 2022) - Dux, F.; Florio, A.; Klarić, J.; Shkerin, A.; Timiryasov, I.
Abstract: We study preheating following Higgs inflation in the Palatini formulation of gravity. We numerically evolve perturbations of the radial mode of the Higgs field and that of three scalars modeling the gauge bosons. We compare the two non-perturbative mechanisms of growth of excitations — parametric resonance and tachyonic instability — and confirm that the latter plays the dominant role. Our results provide further evidence that preheating in Palatini Higgs inflation happens within a single oscillation of the Higgs field about the bottom of its potential, consistent with the approximation of an instantaneous preheating.